2012
DOI: 10.1007/s10957-012-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Advertising and Pricing in a Dynamic Durable Goods Supply Chain

Abstract: Cooperative advertising is an incentive offered by a manufacturer to influence retailers' promotional decisions. We study a dynamic durable goods duopoly with a manufacturer and two independent and competing retailers. The manufacturer, as a Stackelberg leader, announces his wholesale prices and his shares of retailers' advertising costs, and the retailers in response play a Nash differential game in choosing their optimal retail prices and advertising efforts over time. We obtain the feedback equilibrium poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 28 publications
2
29
3
Order By: Relevance
“…On the other hand, the framework of stochastic Stackelberg differential games has found extensive applications in supply chain management. For instance, one may refer to He et al (2009), Chutani and Sethi (2012) and Øksendal et al (2013). Owing to the leadership and followership roles played by reinsurers and insurers, the stochastic Stackelberg differential game would be an ideal framework to model the activity of transferring insurance risk through reinsurance contracts.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the framework of stochastic Stackelberg differential games has found extensive applications in supply chain management. For instance, one may refer to He et al (2009), Chutani and Sethi (2012) and Øksendal et al (2013). Owing to the leadership and followership roles played by reinsurers and insurers, the stochastic Stackelberg differential game would be an ideal framework to model the activity of transferring insurance risk through reinsurance contracts.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that higher profits can be achieved following the implementation of cooperative advertising programs along with a two-part tariff in a channel with a single manufacturer and multiple retailers. Chutani and Sethi (2012) also solved a cooperative advertising model with two retailers. They used a dynamic model that considers prices, retail advertising and coop advertising rates as decision variables, but ignores price competition between retailers.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the e ects of various competitive behaviors on cooperative advertising policies (i.e., competition on price or advertising plans) are investigated. For example, Chutani and Sethi [27] studied a supply chain with a manufacturer and two competing retailers. They assumed that retailers play a di erential Nash game in choosing their strategies; Karray and Zaccour [28] studied a channel including two manufacturers and two retailers in which the national advertising e orts are speci ed as an exogenous parameter instead of decision variable; Zhang and Xie [29] studied a channel with multiple retailers for investigating the impact of the retailer's multiplicity on members' decision and total e ciency.…”
Section: Literature Reviewmentioning
confidence: 99%